Oligonucleotides and G-quadruplex Stabilizers: Targeting Telomeres and Telomerase in Cancer Therapy - Crees, Zachary; Girard, Jennifer; Rios, Zechary; M. Botting, Gregory; Harrington, Kymberly; Shearrow, Caleb; Wojdyla, Luke; L. Stone, Amanda; B. Uppada, Srijayaprakash; T. Devito, Joseph; Puri, Neelu (Current Pharmaceutical Design, 2014)
Cancer is a leading cause of death worldwide and an estimated 1 in 4 deaths in the United States is due to cancer. Despite recent advances in cancer treatment, adverse effects related to cancer therapy remain a limiting factor for many patients. The ideal cancer treatment would selectively target cancerous cells while sparing normal, healthy cells to offer maximal therapeutic benefit while minimizing toxicity. Telomeres are structurally unique DNA sequences at the end of human chromosomes, which play an integral role in the cellular mortality of normal cells. As telomeres shorten with successive cellular divisions, cells develop chromosomal instability and undergo either apoptosis or senescence. In many cancers, this apoptosis or senescence is avoided as normal telomere length is maintained by a ribonucleoprotein reverse transcriptase called telomerase. Telomerase is expressed in more than 85% of all cancers and confers cancerous cells with a replicative immortality, which is a hallmark of malignant tumors. In contrast, telomerase activity is not detectable in the majority of normal somatic cell populations. Therefore, the targeting of telomerase and telomere maintenance mechanisms represent a potentially promising therapeutic approach for various types of cancer. This review evaluates the roles of GRN163L, T-oligo and small molecule G-quadruplex stabilizers as potential anticancer therapies by targeting telomerase and other telomere maintenance mechanisms.
Keywords: tankyrase